Emissions of Nitrous Oxide and Nitric Oxide from Soils of Native and Exotic Ecosystems of the Amazon and Cerrado Regions of Brazil - Eric A. Davidson; Mercedes M.C. Bustamante; Alexandre de Siqueira Pinto (The Scientific World Journal)
This paper reviews reports of nitrous oxide (N2O) and nitric oxide (NO) emissions from soils of the Amazon and Cerrado regions of Brazil. N2O is a stable greenhouse gas in the troposphere and participates in ozone-destroying reactions in the stratosphere, whereas NO participates in tropospheric photochemical reactions that produce ozone. Tropical forests and savannas are important sources of atmospheric N2O and NO, but rapid land use change could be affecting these soil emissions of N oxide gases. The five published estimates for annual emissions of N2O from soils of mature Amazonian forests are remarkably consistent, ranging from 1.4 to 2.4 kg N ha–1 year–1, with a mean of 2.0 kg N ha–1 year–1. Estimates of annual emissions of NO from Amazonian forests are also remarkably similar, ranging from 1.4 to 1.7 kg N ha–1 year–1, with a mean of 1.5 kg N ha–1 year–1. Although a doubling or tripling of N2O has been observed in some young (<2 years) cattle pastures relative to mature forests, most Amazonian pastures have lower emissions than the forests that they replace, indicating that forest-topasture conversion has, on balance, probably reduced regional emissions slightly (<10%). Secondary forests also have lower soil emissions than mature forests. The same patterns apply for NO emissions in Amazonia. At the only site in Cerrado where vegetation measurements have been made N2O emissions were below detection limits and NO emissions were modest (~0.4 kg N ha–1 year–1). Emissions of NO doubled after fire and increased by a factor of ten after wetting dry soil, but these pulses lasted only a few hours to days. As in Amazonian pastures, NO emissions appear to decline with pasture age. Detectable emissions of N2O have been measured in soybean and corn fields in the Cerrado region, but they are modest relative to fluxes measured in more humid tropical agricultural regions. No measurements of NO from agricultural soils in the Cerrado region have been made, but we speculate that they could be more important than N2O emissions in this relatively dry climate. While a consistent pattern is emerging from these studies in the Amazon region, far too few data exist for the Cerrado region to assess the impact of land use changes on N oxide emissions.